Pervious Concrete for Urban Stormwater Management in Kathmandu Valley - Bhattarai, Bibek; Bhattarai, Bikram Singh (Journal of Sustainability and Environmental Management, 2023)
Urban drainage difficulties have sparked debates and conflicts because of population growth and land use. Expanding urban infrastructure has led to an increase in impermeable zones, which prevent water from seeping into the ground and percolating. Rapid urbanization, population growth, and climate change have put strain on water management in Kathmandu Metropolitan City (KMC). Urban flooding is becoming more frequent, which has a negative impact on daily life and causes major damage. This study assesses the possibilities for controlling runoff volume through stormwater management in Kathmandu Metropolitan City (KMC). To counteract floods brought on by urbanization, pervious concrete, a substance that allows water to seep through floors or seams, is essential. Dosing strategies must be used, concentrating on aggregate content and water/cement ratio (water/cement (w/c)), to obtain acceptable traces. The purpose of this study is to evaluate permeable concrete’s effectiveness as a flood-prevention alternative. A review of books, journals, monographic works, and standards is included as part of a bibliographical research project. The strengths of the previous concrete ranged from 2.8 to 28 MPa, according to data gathered after 28 days, falling within the normal range of ACI 522R:06 (2006) and below the normal range of 10 MPa. The porous concrete successfully percolated precipitated water in just a short period, demonstrating its potential as a successful substitute for flood prevention.